What is Sociology of Space? Definition and Scope of Study - Ahmadin, Mr. (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2025)
This paper discusses the sociology of space which is a part or extension of sociology that uses geographical theories, especially human geography, economic geography, and feminist geography. The scope of the study targets various social practices, the dynamics of the power of social institutions and spatial dialectics as a form of human interaction with space. This type of research is descriptive research using data obtained from studies of various literature both in scientific journal articles, popular scientific articles, books, and other types of written works. As a library research, data analysis is carried out by comparing it with other sources that study similar contexts. The results of the study show that for quite a long time, the sociology of space has played an important role and contributed positively in providing a new nuance to the study of social sciences and even space is considered an important part of the process of forming sociological theories. The interdisciplinary characteristics of the sociology of space, in its development, are greatly inspired by the theories of Marxism and Postcolonialism and in the scope of its study there is much overlap with geography and architecture.